Knowledge frontiers: The concept of mechanobiology applied to strength training - Formicola, D. (EWF Scientific Magazine, 2019)
In the classical theory of training programming, an annual training plan generally begins with a preparatory period dedicated to general anatomical adaptation. The connective, myofibrillar and skeletal remodelling that takes place in this period, makes it possible to predispose the bones, ligaments, tendons, muscles and heart to respond more quickly to the mechanical stresses produced by the loads and technical exercises planned for the following competitive period. For the consequences due to the detraining process, it is imperative to remember that the greater number of months that the preparatory period lasts, the more the anatomical adaptation achieved will remain stable during the subsequent competitive period. An example of an annual plan of this type, aimed at athletes of strength and power sports, is divided into five phases, three in the preparatory period - (1) muscle development, (2) strength, (3) power -and two in the competitive one - (4) development of maximum performance and (5) maintenance of the maximum level of performance. An annual plan structured in this way envisages increasing the muscle mass (in phase 1), increasing its strength (in phase 2), to be used (in phase 3) as the basic physical condition for the development of power, which will serve (in phase 4) to quickly reach the maximum performance peaks that will finally be consolidated, stabilised and made routine (in phase 5). To achieve the anticipated muscular adaptation, in the preparatory period, and the transfer of its effects to performance, in the competitive period, the mechanical stimulations (exercises) inserted in the five phases will progressively produce a decrease in volume and an increase in intensity. From 3-6 sets of 10-15 repetitions with loads of 50-75% compared to the maximum, which stimulate the muscular hypertrophy sought in phase 1, we move on to 3-5 sets of 4-8 repetitions with loads around 80- 90% of the maximum to increase the maximum force, which is the goal of phase 2. In phase 3 of the preparatory period, the speed of execution of the exercises to train the power is increased, with 3-5 sets of 2-5 repetitions and loads of 75- 95% of the maximum. Finally, entering phase 4, the competitive period begins and so only 1-3 sets of 1-3 repetitions are performed with loads exceeding 90% of the maximum. In this phase, athletes aim at achieving a new personal record and, having reached this, they move on to phase 5 where they perform 2-3 sets of 6-8 repetitions with loads of 80-85% of the new maximum. The logical sense underlying this annual plan model completely satisfies the principle of the cumulative effects of anatomical adaptation. However, by applying the mechanical principles of detraining and cyclic hysteresis, we can highlight some critical points. In the phase dedicated to muscle development (phase 1) the muscles are subject to hypertrophy. The myofibrils contractile filaments thicken, the sarcoplasm becomes denser and is enriched with water, salts and energy substrates. The sarcomeric cytoskeleton thickens and branches. Intracellular frictions and mechanical strengths increase, as does the energy cost of the flow of intrasarcomeric protein filaments and of the stacking of intracellular sarcomeres. The overall effect of this remodelling will reduce the speed of muscle contraction. In the subsequent phase, dedicated to maximum force (phase 2), the mechanical stimuli that reach the muscle cells become more intense and less frequent. By prolonging the recovery time between the series, the muscle fibres have more time to oxygenate and the cellular processes of hypoxia-related hypertrophy are minimised. Furthermore, the reduction in the number of repetitions to be performed in the set leads the muscle cells to choose the fastest bioenergetic processes based on phosphates, and discard the slower ones of glycolytic substrates. Under these conditions, the enzymatic processes linked to the use of the energy pathways of sugars and fats are degraded and the cellular recovery capacity is reduced overall. However, by continuing to receive intense mechanical stimuli from the extreme overloads of this period, the myofibrils keep their protein assets intact, they continue to strengthen their contractile and support structures, while they begin to lose the volume of surplus energy substrates, thus becoming resistant at infrequent maximum loads. The preparatory period is completed with the development of power, choosing to perform explosively maximum force exercises and technical competition movements. To prevent the onset of fatigue from slowing down the execution, each set must be carried out with a few repetitions. Recovery can be reduced, if mental concentration tends to be easily lost, or prolonged, if energy stocks are slowly restored. The choice to increase the loads, set after set, depends on the speed of execution, which must remain constant and maximal with each repetition. In the development phase of maximum performance, the first phase of the competitive period, mechanical stimulations are generated mainly by the specific exercises used to improve competition performance. These exercises, and their variants, are biomechanically and neurologically very complex, performed in a very short time, contracting a high number of muscles. The more they are repeated in training, the more their technical and metabolic efficiency improves. Performing them continuously and at high speed requires a very high energetic, muscular and mental effort. Therefore, it is possible to choose to perform just a few sets, with a few repetitions for several sessions a day. However, the previous training period has developed a reduced capacity for recovery based on slow aerobic processes. Furthermore, the increase in overloads, which began during the period of muscular development and continued in the subsequent period of maximum strength, has always occurred at sub-maximum speeds. Finally, the only period dedicated to power was not enough to learn how to perform the race movements at maximum speeds. Therefore, in the competitive period it becomes difficult to increase the frequency of training without producing an excess of cellular over-stimulation, an acute inflammatory state, a debilitating condition, a psychophysical refusal to train, an overtraining condition and a greater predisposition to injuries. This brings us to the final phase of the annual plan, which aims to replicate the performance at maximum power several times, with the nervous and muscular systems in unsuitable conditions to create explosive movements and recover immediately. Without resilience and rapid muscle contractions, you cannot complete a volume of work sufficient to produce stable improvements in the performance power of technical movements. Avoiding the processes of detraining and cyclic hysteresis, when planning training programmes, can lead to not achieving the expected results. If you look for a parameter that must have constant growth throughout the training plan, instead of choosing the multiform parameter of muscle strength, there is the alternative of the most undifferentiated speed of execution of technical movements. In the preparatory period, for example, after a brief phase of learning correct movements, one can focus on increasing speed and load in parallel on a large number of different exercises, all derived from specific technical movements39. If, for each of these exercises, the speed of the competition movement is reached and exceeded, the mechanostimulations that stimulate the genetic transcription of the muscle fibres will produce a more suitable myofibillary remodelling to contract quickly. Continuing with the example, in the competitive period, instead, it is possible to decide to increase speed and load exclusively for the technical competition movement. In this programming mode, it can be performed a few times a week, to avoid overtraining the memory patterns that form it and to bring the myofibrils of the muscles involved in its realisation into an acute inflammatory state. In this last period, the training volume is guaranteed by the choice to perform many times a week, keeping the execution speed high, a few exercises which are useful in correcting the most recursive technical defects. This change of perspective fully satisfies the needs of modern sport of weightlifting, record after record, the expressions of muscular power.